Microsimulation Study on Energy Release and Rock Block Ejection Force of Granite under Different Unloading Conditions - Wang, Xin-Yuan; Yin, Yan-Chun; Xing, Ming-Lu; Zhang, Dong-Dong; Chen, Yang; Wang, En-Chao (Frontiers in Earth Science, 2022)
Rock burst is one typical dynamic disaster caused by excavation in deep underground engineering. High stress unloading test is a common research method for rock burst. Due to the limitation of laboratory test conditions, it is difficult to monitor the energy release and dissipation information during rock burst in unloading test. But the study of energy evolution law is more helpful to reveal the essential characteristics of rock burst. Therefore, the energy evolution process and ejection failure characteristics of granite after unloading were analyzed through the unloading simulation test in this paper, and the influence of unloading velocity, lateral stress and axial stress were researched. The micro structure numerical model of the granite was established by using digital image processing technology and PFC2D software, aiming to match the real granite. The energy evolution process of unloading granite can be divided into three stages, namely whole energy rapid release stage, side wall energy slow release stage, and rock block ejection stage. The area near the unloading side wall is the main energy release and rock block ejection area. In the whole energy rapid release stage, the energy release velocity and dissipation velocity show similar law, i.e. a positive power function correlation with unloading velocity, a negative power function correlation with lateral stress, and a positive linear function correlation with axial stress. In the rock block ejection stage, with increasing of the unloading velocity and axial stress, the rock block ejection force increases as a power function, while it decreases with increasing of lateral stress. This research is an important supplement to the laboratory unloading test. It has theoretical guiding significance for rock burst hazard assessment during excavation in deep underground engineering.